THE INFLUENCE OF BLENDED LEARNING ON STUDENTS LEARNING OUTCOMES IN ENGLISH SPEAKING SKILL GREETINGS MATERIAL - Livia Hesti Parante; Nihta V.F. Liando; Fivy Andries (Program Studi Pendidikan Bahasa Inggris, 2022)
This research aims at the influence is being found in blended learning method towards students learning outcomes. This research utilized a quasi-experimental research with experimental group and control group. This research was conducted to the seventh grade students of SMP Negeri 1 Tomohon in the academic 2020-2021. The subjects of this study are 40 students. For the experimental group there are 20 students and in the control group there are 20 students. The data were collected through test given to the both groups. Blended learning can be used to develop students’ learning outcomes in English speaking skill greeting material. It can be seen from the students’ score of experimental group is higher than control group. The mean score of the experimental group is 85, 15 and the mean score of the control group is 45, 35. It can be concluded that blended learning method have a significant impact on students’ learning outcomes in English speaking skill greeting material.